Effects of oral anticoagulation for atrial fibrillation after spontaneous intracranial haemorrhage in the UK: a randomised, open-label, assessor-masked, pilot-phase, non-inferiority trial. Issue 10 (October 2021) - ,; Al-Shahi Salman, Rustam; Keerie, Catriona; Stephen, Jacqueline; Lewis, Steff; Norrie, John; Dennis, Martin S.; Newby, David E.; Wardlaw, Joanna M.; Lip, Gregory Y.H.; Parry-Jones, Adrian; White, Philip M.; et al.
Summary: Background: Oral anticoagulation reduces the rate of systemic embolism for patients with atrial fibrillation by two-thirds, but its benefits for patients with previous intracranial haemorrhage are uncertain. In the Start or STop Anticoagulants Randomised Trial (SoSTART), we aimed to establish whether starting is non-inferior to avoiding oral anticoagulation for survivors of intracranial haemorrhage who have atrial fibrillation. Methods: SoSTART was a prospective, randomised, open-label, assessor-masked, parallel-group, pilot phase trial done at 67 hospitals in the UK. We recruited adults (aged ≥18 years) who had survived at least 24 h after symptomatic spontaneous intracranial haemorrhage, had atrial fibrillation, and had a CHA2 DS2 -VASc score of at least 2. Web-based computerised randomisation incorporating a minimisation algorithm allocated participants (1:1) to start or avoid long-term (≥1 year) full treatment dose open-label oral anticoagulation. The participants assigned to start oral anticoagulation received either a direct oral anticoagulant or vitamin K antagonist, and the group assigned to avoid oral anticoagulation received standard clinical practice (antiplatelet agent or no antithrombotic agent). The primary outcome was recurrent symptomatic spontaneous intracranial haemorrhage, and was adjudicated by an individual masked to treatment allocation. All outcomes were ascertained for at least 1 year after randomisation and assessed in the intention-to-treat population of all randomly assigned participants, using Cox proportional hazards regression adjusted for minimisation covariates. We planned a sample size of 190 participants (one-sided p=0·025, power 90%, allowing for non-adherence) based on a non-inferiority margin of 12% (or adjusted hazard ratio [HR] of 3·2). This trial is registered with ClinicalTrials.gov (NCT03153150 ) and is complete. Findings: Between March 29, 2018, and Feb 27, 2020, consent was obtained at 61 sites for 218 participants, of whom 203 were randomly assigned at a median of 115 days (IQR 49–265) after intracranial haemorrhage onset. 101 were assigned to start and 102 to avoid oral anticoagulation. Participants were followed up for median of 1·2 years (IQR 0·97–1·95; completeness 97·2%). Starting oral anticoagulation was not non-inferior to avoiding oral anticoagulation: eight (8%) of 101 in the start group versus four (4%) of 102 in the avoid group had intracranial haemorrhage recurrences (adjusted HR 2·42 [95% CI 0·72–8·09]; p=0·152). Serious adverse events occurred in 17 (17%) participants in the start group and 15 (15%) in the avoid group. 22 (22%) patients in the start group and 11 (11%) patients in the avoid group died during the study. Interpretation: Whether starting oral anticoagulation was non-inferior to avoiding it for people with atrial fibrillation after intracranial haemorrhage was inconclusive, although rates of recurrent intracranial haemorrhage were lower than expected. In view of weak evidence from analyses of three composite secondary outcomes, the possibility that oral anticoagulation might be superior for preventing symptomatic major vascular events should be investigated in adequately powered randomised trials. Funding: British Heart Foundation, Medical Research Council, Chest Heart & Stroke Scotland.